2022
DOI: 10.1186/s12891-022-06078-y
|View full text |Cite
|
Sign up to set email alerts
|

Soft tissue stabilization of the hinge position in medial closed wedge distal femoral osteotomy: an anatomical study

Abstract: Background Soft tissue has an important role in stabilizing the hinge point of medial closed wedge distal femoral osteotomy (MCWDFO). However, there are conflicting data on the soft tissue anatomy around the hinge point of MCWDFO and, therefore, further anatomical data are needed. The purposes of the study were to: 1) anatomically analyze the soft tissue around the hinge point of MCWDFO; 2) radiologically define the appropriate hinge point to prevent an unstable hinge fracture based on the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 23 publications
3
14
0
Order By: Relevance
“…Therefore, they recommend the proximal border of the lateral femoral condyle as the ideal hinge position based on soft tissue coverage and bone density. Oda et al meticulously examined the lateral distal femur, focusing on the periosteum and joint capsule, using human cadavers [ 15 ]. They found that the thickness of the periosteum changed at the border region between the metaphysis and diaphysis, which can be determined as the turning point of the curve of the lateral distal femur on the radiograph, and markedly decreased in the diaphyseal region.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they recommend the proximal border of the lateral femoral condyle as the ideal hinge position based on soft tissue coverage and bone density. Oda et al meticulously examined the lateral distal femur, focusing on the periosteum and joint capsule, using human cadavers [ 15 ]. They found that the thickness of the periosteum changed at the border region between the metaphysis and diaphysis, which can be determined as the turning point of the curve of the lateral distal femur on the radiograph, and markedly decreased in the diaphyseal region.…”
Section: Discussionmentioning
confidence: 99%
“…Procedures used on the femur include medial closed wedge osteotomy or lateral open wedge osteotomy [4, 20, 32, 40, 47]. There is no existing evidence whether the lateral opening wedge or the medial closing wedge technique leads to better clinical outcome [25, 30, 50]. Although there are several publications which reported on comparable results after DFO and lateral unicompartimental knee arthroplasty [34] and encouraging results regarding sports activities [7], no reports of the influence of joint angles are available.…”
Section: Introductionmentioning
confidence: 99%
“…8,13,20 Therefore, several studies have attempted to define the ''safe zone'' for intracapsular-extra-articular osteotomy around the knee in which the risk of unstable hinge fracture is minimized and there is no risk of cutting into the joint space in the distal direction. 6,14,15,18 The local soft tissue reportedly plays an important role in stabilizing the hinge point of osteotomy around the knee. In MOWHTO, the joint capsule-periosteal sleeve and the tibialis anterior muscle work as soft tissue stabilizers in the region from the tip of the fibular head to the circumference line of the fibular head, and this area has been termed the ''safe zone.''…”
mentioning
confidence: 99%
“…6,15 Furthermore, we have previously reported that the periosteum supports the hinge of medial closing-wedge distal femoral osteotomy (MCWDFO) within the area surrounded by the apex of the turning point of the femoral metaphysis and the upper border of the posterior part of the lateral femoral condyle. 18 In addition to these soft tissues, the tendon attachments act as an anchor that is expected to stabilize the hinge point. The enthesis of the tendon is classified into 2 categories depending on the presence or absence of a fibrocartilaginous layer and is expressed as having ''direct'' or ''indirect'' insertion.…”
mentioning
confidence: 99%
See 1 more Smart Citation